RETRACTED: Greening of higher education: Global thinking, local initiative - Djoldosheva Tamara; Mottaeva Angela; Pervukhina Irina; Vidrevich Marina; Berezhnova Elena (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001